Microbiome engineering: unlocking therapeutic potential in inflammatory bowel disease - Kong, Chen; Huang, Long-bin; Yang, Mei-feng; Yue, Ning-ning; Luo, Duo; Zhang, Yuan; Tian, Cheng-mei; Song, Yang; Wei, Dao-ru; Shi, Rui-yue; Liang, Yu-jie; Yao, Jun; et al. (Frontiers in Microbiology, 2025)
The human gut microbiome, traditionally linked to infectious diseases, is now recognized as a hub of non-pathogenic microorganisms that play pivotal roles in host communication and homeostasis. Advances in microbiome engineering have enabled the design of “smart” living therapeutics for inflammatory bowel disease (IBD), leveraging engineered symbiotic bacteria, yeasts, and bacteriophages. This review synthesizes recent progress in reprogramming microbes using synthetic biology tools, emphasizing their capacity to sense pathological signals and deliver targeted therapies. We critically evaluate three key approaches: synthetic gene circuits in bacteria for precision drug delivery, phage-mediated modulation of dysbiotic microbiota, and yeast-based systems for metabolic intervention (e.g., butyrate production). Challenges in biocontainment, genetic stability, and clinical translation are discussed, alongside emerging strategies such as outer membrane vesicles (OMVs) for immunomodulation. By distilling these advances, we highlight a roadmap for translating engineered microbes into safe and effective IBD therapies.